Determinants of Organizational Commitment: The Roles of Employee Empowerment, Self Efficacy, and Perceived Organizational Support in Public Institutions - Prianti, Rita; Sari, Laynita; Septiano, Renil; Afriyeni, Afriyeni; Susanti, Elvi; Rusita, Indah; Oktavora, Oga Gandradika (AIBPM Publisher, 2025)
Organizational commitment is crucial to enhancing the performance of employees and the efficiency of the institutions of the public sector. Nevertheless, the issues of low engagement, lack of participation, and motivation remain problematic to many government organizations. These concerns underscore the need to explore psychological and structural aspects that determine the development of attachment by employees towards their place of work. This paper explores how employee empowerment, self efficacy and perceived organizational support affect organizational commitment in a local government organization. The quantitative method was employed to collect data on 78 employees via a structured questionnaire and to analyze it with the help of the multiple linear regression. The findings indicate that organizational commitment is significantly enhanced with the empowerment of employees and self efficacy, whereas organizational support positively though not very strong. The three variables combined can account 66.7% of organizational commitment variance. The results highlight the necessity to tighten the participatory working conditions, build trust in the employees to use their skills, and develop better support systems within organizations. Such implication give recommendations to leaders in the public sector who want to ensure that they have a more committed, motivated, and resilient workforce